Incentives and drivers for property owners to pursue private embedded generation through solar photovoltaic systems - Scholtz, Michelle (Department of Construction Economics and Management, 2025)
South Africa has been experiencing an energy crisis for over sixteen years, leading to an increase in the frequency and duration of power cuts. The energy crisis has a detrimental impact on the country's economy, and consequently, on residential and non-residential private property owners. Furthermore, the country is heavily reliant on coal for energy generation, which requires the move towards a more sustainable energy mix. Renewable energy generation, especially in the form of rooftop solar photovoltaic (PV) systems, is expected to play an important role in South Africa's future energy systems. The national government, along with various municipalities at local government level, are introducing regulatory incentives to promote the uptake of solar PV systems in the private sector. These incentives include feed-in tariffs, capital subsidies and tax benefits. In addition to the regulatory incentives, there are non-regulatory drivers that motivate private property owners to pursue solar PV systems. These drivers include environmental considerations, cost savings, energy security, tenant requirements, and green-energy finance. This study examines the various regulatory incentives available to private property owners located in the City of Cape Town (CoCT) to pursue solar PV systems. The CoCT was selected as a single case study as the municipality creates a conducive environment through their regulatory framework for private property owners to pursue private embedded generation systems. The report examines the different incentives applicable to residential and non-residential property owners. The research also establishes to what extent the regulatory incentives influence private property owners to pursue solar PV systems, when compared to non-regulatory drivers and benefits. A literature review was conducted and the respondents were interviewed to determine the extent of national and municipal regulatory incentives available to residential and non-residential private property owners and whether these incentives are considered a determining factor in pursuing solar PV systems, when compared to non-regulatory drivers. The study revealed that the various regulatory incentives differ somewhat for residential and non-residential property owners. These differences impact the extent to which the regulatory incentives motivate particular private property owners to pursue solar PV systems. The research suggests that, although the regulatory incentives play a significant role in private property owners' decision-making process, the non-regulatory drivers are considered to be the main motivating factor for private property owners pursuing solar PV systems.